Percutaneous fixation of scaphoid fractures. An anatomical study. - Kamineni, S; Lavy, C (1999)
Percutaneous scaphoid fracture fixation has many advantages over the open method of fixation. We describe the anatomical basis for a safe percutaneous approach. Cannulated screws were inserted into 32 cadaveric scaphoids through 1 cm palmar incisions under fluoroscopic control. We then measured the distance between the entry point in the scaphoid and important local neurovascular structures. We also measured the angle of entry of the guide wire in two planes. The mean distance of the entry point from the main radial artery was 14 mm (range, 7-24 mm); from the radial nerve 19 mm (range, 7-35 mm); from the recurrent branch of the median nerve 29 mm (range, 14-45 mm); and from the superficial branch of the radial artery 5 mm (range, 0-8 mm) The mean radial angle of insertion was 34 degrees and the mean palmar angle of insertion was 58 degrees. Percutaneous fixation of scaphoid fractures puts the superficial palmar branch of the radial artery at risk. We recommend a 1 cm incision centred over the scaphotrapezial joint and dissection under direct vision to the entry point in the scaphoid rather than a completely percutaneous approach.